Lysine Acylation Modification Landscape of Brucella abortus Proteome and its Virulent Proteins - Zhang, Xi; Chen, Jingjing; Dong, Qiao; Zhu, Jinying; Peng, Ruihao; He, Chuanyu; Li, Yuzhuo; Lin, Ruiqi; Jiang, Pengfei; Zheng, Min; Zhang, Huan; Liu, Shiwei; et al. (Frontiers in Cell and Developmental Biology, 2022)
The myriad of posttranslational modifications (PTMs) of proteins that occur in all living cells are crucial to all kinds of biological processes. Brucella is an intracellular parasitic bacterium that can cause chronic diseases in both humans and livestock. To reveal the relationship between PTMs and the virulence and survival of Brucella, we described the first comprehensive multiple PTM-omics atlas of B. abortus 2308. Five PTMs involving lysine, namely 2-hydroxyisobutyrylation, succinylation, crotonylation, acetylation, and malonylation were identified. Nearly 2,000 modified proteins were observed, and these proteins took part in many biological processes, with a variety of molecular functions. In addition, we detected many significant virulence factors of Brucella among the modified proteins. 10 of the 15 T4SS effector proteins were detected with one or more PTMs. Moreover, abundant PTMs were detected in other typical virulence factors. Considering the role of PTMs in various biological processes of Brucella virulence and survival, we propose that the virulence of Brucella is associated with the PTMs of proteins. Taken together, this study provides the first global survey of PTMs in Brucella. This is a prospective starting point for further functional analysis of PTMs during the survival of Brucella in hosts, interpretation of the function of Brucella proteins, and elucidation of the pathogenic mechanism of Brucella.